Markowitz efficient frontier and capital market line : evidence from the portuguese stock market - Garcia, Maria Teresa (2017)
This paper estimates the efficient frontier and the capital market line using listed stocks of the Portuguese capital market that are part of the PSI20 index, considering two different periods - before and after the 2008 financial crisis, known as the Global Financial Crisis. The results show the impact of the 2008 financial crisis on the global minimum variance portfolio and on the market portfolio. The sensitivity analysis of the results to the inclusion or not of the year 2008 is also considered